Arginine Metabolism and Its Potential in Treatment of Colorectal Cancer - Du, Tao; Han, Junyi (Frontiers in Cell and Developmental Biology, 2021)
Colorectal cancer is the leading cause of death from cancer globally. The current treatment protocol still heavily relies on early detection and surgery. The molecular mechanisms underlying development of colorectal cancer are clinically important and determine the prognosis and treatment response. The arginine metabolism pathway is hyperactive in colorectal cancer and several molecules involved in the pathway are potential targets for chemoprevention and targeted colorectal cancer therapy. Endothelial nitric oxide synthase, argininosuccinate synthetaseand ornithine decarboxylase (ODC) are the main enzymes for arginine metabolism. Limiting arginine-rich meat consumption and inhibiting ODC activity largely reduces polyamine synthesis and the incidence of colorectal cancer. Arginine transporter CAT-1 and SLC6A14 are overexpressed in colorectal cancer cells and contributes to intracellular arginine levels. SLC38A9 serves as a component of the lysosomal arginine-sensing machinery. Pharmaceutical inhibition of single enzyme or arginine transporter is hard to meet requirement of restoring of abnormal arginine metabolic network. Apart from application in early screening for colorectal cancer, microRNA-based therapeutic strategy that simultaneously manipulating multiple targets involved in arginine metabolism brings promising future in the treatment of colorectal cancer.